The Role Of Instagram In Constructing The Ideal Mother - Shulbi Putri; Neni Yulianita; Ferry Darmawan (UPT Publikasi Ilmiah UNISBA, 2025)
Motherhood has increasingly become a topic shaped and negotiated in digital spaces, especially on social media. This study examines how Instagram shapes the construction of the